The Witching Place: A Perilous Page (A Curious Bookstore Cozy Mystery-Book 3) - Sophie, Love (Lukeman Literary, 2021)
"The perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (For Now and Forever) THE WITCHING PLACE: A PERILOUS PAGE is book #3 in a charming new cozy mystery series by bestselling author Sophie Love, author of The Inn at Sunset Harbor series, a #1 Bestseller with over 200 five-star reviews. When Alexis Blair, 29, is fired from her book publishing job and breaks up with her boyfriend on the same day, she wonders if life is urging her to make a fresh start. She decides it's time to pursue her lifelong dream of opening a bookstore of her own-even if that means leaving Boston and accepting a job in a curious bookstore in a small seaside town an hour away. A cryptic visitor comes into town, looking for a rare book, and willing to pay anything. But when he ends up dead, Alexis wonders: was the price too high? And did Alexis's mysterious store owner have anything to do with it? A page-turning cozy, rife with the supernatural, mystery, secrets and love-and centered around a small town as odd and endearing as its shop-A PERILOUS PAGE will make you fall in love and keep you laughing out loud as you turn pages late into the night. "The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews (For Now and Forever)
Keywords: Krimi, detektivky